The Existence of Equilibrium in a Financial Market with Transaction Costs - Xing Jin; Frank Milne (Queen's University, Department of Economics, 1996)
This paper proves the existence of a general equilibrium in a financial model with transaction costs. The general equilibrium is shown to exist in a model with convex trading technology, in which the agents include consumers, production firms, brokers and dealers. When the trading technology is non-convex, an individual approximate equilibrium, introduced by Heller and Starr (1976), is proved in the above model. And, moreover, under a further assumption of finitep-convexity on the commodity excess demand correspondence, the general equilibium for a non-convex exchange economy is obtained for an economy with consumers, brokers and dealers.
Keywords: C62; D51; G10; 330; arbitrage; general equilibrium; transaction cost; individual approximate equilibrium; finite p-convexity